Development Of Picture Storybooks Based On Scientific Approaches In Science Lessons Class V Sdn 36 Mataram Academic Year 2023 - Baiq Nidya Rizki Karima Karima (Journal of Law and Social Politics, 2023)
The main target of education is to improve quality human resources. Quality human resources will be achieved if they have the ability, namely broad knowledge, mastery of knowledge involved and a professional mental attitude and have the spirit or motivation to achieve. This research is a type of development research (Research and Development). What was developed in this study is a scientifically-based picture story book in grade V elementary school science lessons. This research is a research on the development of picture storybooks based on a scientific approach for grade V elementary school. The process of developing picture storybooks based on a scientific approach for grade V elementary school includes the type of Research and Development (R&D) development with a 4D model, namely: (1) Define which consists of (a) conducting a needs analysis, (b) determining learning objectives, and (c) determining the learning content and sequence of storybook stories